The Communities Care programme: changing social norms to end violence against women and girls in conflict-affected communities. Issue 2 (3rd May 2016) - Read-Hamilton, Sophie; Marsh, Mendy
ABSTRACT: While significant progress has been made in recent years in responding to violence against women and girls in humanitarian contexts, timely and quality care and support to survivors still remains a challenge. Little is known about effective prevention. Few interventions have targeted underlying drivers of violence against women and girls (VAWG), which include social norms. In response to the urgent need to increase access to services for survivors, as well as the imperative to develop and test effective strategies to actually prevent VAWG in conflict-affected communities, UNICEF has developed the Communities Care: Transforming Lives and Preventing Violence programme. An innovative and holistic initiative currently being piloted in internally displaced camps and communities in Somalia and South Sudan, the Communities Care programme is premised on the idea that while armed conflict causes horrendous suffering, the changes created to community structure, economic roles, and social dynamics offer an opportunity to promote social norms that uphold women and girls' equality, safety, and dignity. While the pilot phase is ongoing throughout 2016, indications to date are positive. The preliminary analyses of data suggest promising trends, with the intervention communities having significantly greater improvement than the control communities on some of the dimensions of social norms measured. Communities Care programme is also promoting community actions against violence in pilot sites. Evidence and lessons from Communities Care will contribute to the refinement of efforts to prevent and respond to VAWG in conflict-affected settings around the world.